Q: Evaluate each expression (7 -3)² plus (7 plus 1)²?

Write your answer...

Submit

Related questions

You don't "solve" an expression. You can solve an equation; an expression can be simplified or otherwise manipulated, and if you know the value of "x" (in this case), you can evaluate its value.

b + 1 is b plus 1 as an algebraic expression.

1/2w+2

It evaluates to: 12+(-1)+(-1)+3 = 13

xy + x + y + 1 is an expression, not an equation. An expression cannot be solved.

Put n = 1, 2, 3, 4 etc in the expression 5n + 2 and evaluate to get the sequence.

2!

You have to substitute a value for the letter variable in the expression. This is what we call evaluating the algebraic expression. An example would be 3x+1=7, when x=2.

The answer is b+1. Therefore the algebraic expression for this is b+1

You cannot. What you have in the question is an expression. An expression cannot be proven. You need an equation (or inequality).

You have to substitute a value for the letter variable in the expression. This is what we call evaluating the algebraic expression. An example would be 3x+1=7, when x=2.

Both - a polynomial expression, if you like.

The expression written in the question is the rational expression.

(3x2 + 2x + 1)

3(10x + y) + 2x + 7y (multiply the 3 through the parentheses then combine like terms) = 30x + 3y + 2x + 7y = 32x + 10 y Evaluate an expression for some values of x and y, means to substitute those values into the expression, such that when x = 3 and y = 1 the value of the given expression is 106: 32x + 10y = 32(3) + 10(1) = 96 + 10 = 106

14

It means: 1/10 times 3.7 = 0.37

There are 5 terms in the given expression

When you have an algebraic expression with variables in it, you need to know the the value of each variable. The value of the expression is found by replacing the variables with their values and simplifying. For example, evaluate 2xy-3x if x=5 and y=-1. 2xy-3x = 2*5*(-1) -3*5 = -10-15 = -25.

It is an expression and can be simplified to: 3d+f+1

x does not equal -1, because if x is minus 1, x plus 1 is zero and division by zero is not defined.

2m + 1

An algebraic expression

It is a quadratic expression and when factored is: (x+1)(x+1)

When simplified it is just: 1

Study guides